Education and technology for a better world 9th IFIP TC 3 World Conference on Computers in Education, WCCE 2009, Bento Gonçalves, Brazil, July 27-31, 2009, proceedings - IFIP TC 3 World Conference on Computers in Education (IFIP Advances in information and communication technology, 2009)
This book constitutes the refereed proceedings of the 9th IFIP TC 3 World Conference on computers in Education, WCCE 2009, held in Bento Gonçalves, Brazil, in July 2009. The 48 revised full papers were carefully reviewed and selected from 146 full papers accepted for the conference during four rounds of reviewing. The conference received 289 submissions in total. The papers are organized in topical sections on innovation and creativity in schools; informatics; digital solidarity; learners and life long learning; networking and collaboration; and teaching and the role of teachers. Invited papers from Brazil - Scientific and technological education in Brazil: advancements and challenges for the 21st Century - NASA education and educational technologies exemplified by the space weather action center program - Evaluation of distance course effectiveness - Exploring the quality of interactive processes - Innovation and creativity in schools - The impact of the multi-sensory program alfabeto on the development of literacy skills of third stage pre-school children - Personalized e-learning environments: considering students’ contexts - Software Junctus: joining sign language and alphabetical writing - Innovative teaching/learning with geotechnologies in secondary education - A new virtual and remote experimental environment for teaching and learning science - Investment in information and communication technologies in the irish education sector - Pyramids in logo: a school project in ‘search’ of the fourth dimension - Towards transformation: alwaysOn students and health education - Virtual cities as a collaborative educational environment - ICT action school development at Helen Parkhurst Dalton school, Part II - E-maturity and school development: When the tail wants to wag the dog - Toward a learning/instruction process model for facilitating the instructional design cycle - The making of an online masters program in the North American context - Informatics - CV-Muzar using a multiagent system for group formation - The development of educational games supported by a pedagogical tutor agent - Applying informatics knowledge to create 3D worlds - Digital solidarity - Ensuring success and quality through the use of standards in team projects: students’ perceptions - Implementing and sustaining educational change and ICT: a case study of a taiwanese primary school - The Mexican National Programs on teaching mathematics and science with technology: the legacy of a decade of experiences of transformation of school practices and interactio The Mexican National Programs on teaching mathematics and science with technology: the legacy of a decade of experiences of transformation of school practices and interactions - Trust and conflicts in distance learning higher education courses tutor teams - Learners and life long learning - Bridging the digital divide, aiming to become lifelong learners - Evolution of information systems curriculum in an Australian University over the last twenty-five years - Secondary school students’ english writing aided by spelling and grammar checkers - Learning design for creating a lifelong learning organization - Open virtual worlds as pedagogical research tools: learning from the schome park programme - Technology mentoring: research results across seven campuses - So I sat down with my mother: connectedness orientation and Pupils’ independence - Preparing graduate students for industry and life long learning: a project based approach - Advanced Networks in Dental Rich Online MEDiA (ANDROMEDA) - A competency-based learning resource retrieval process: The LUISA-UHP case-study - Networking and collaboration - Is there a role for social networking sites in education? - Collective text editor: a new interface focused on interaction design - An open-source learning content management and assessment system - Supporting collaborative learning activities with a digital library and annotations - Using Cultural Historical Activity Theory (CHAT) to frame ‘SuperclubsPLUS’, an online social network for children - Using text-mining to support the evaluation of texts produced collaboratively - PLME as a cognitive tool for knowledge achievement and informal learning - Growing a peer review culture among graduate students - Teaching and the role of teachers - Computers in the teaching of english as a foreign language: access to the diversity of textual genres and language skills - School a study on pedagogical requirements for multi-platform learning objects Podcasts in higher education: students’ and lecturers’ perspectives - Design patterns for the use of technology in introductory mathematic - Tutors - Learning by peers: an alternative learning model for digital inclusion of elderly people - Teachers’ perceptions about the barriers and catalysts for effective practices with ICT in primary schools - Transformative personal development: helping teachers to thrive on discontinuous change.